PENERAPAN METODE PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN TIK UNTUK MENINGKATKAN MOTIVASI SISWA KELAS IX MTs. NURUL YAQIN APPATANAH - Aprianti; Mustari S. Lamada; Anas Arfandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted to examine the extent to which the implementation of interactive learning methods can enhance the learning motivation of Grade IX students in the Information and Communication Technology (ICT) subject at MTs. Nurul Yaqin Appatanah. The research employed a Classroom Action Research (CAR) approach carried out in two cycles, with each cycle consisting of the stages of planning, implementation, observation, evaluation, and reflection. The research subjects were 30 Grade IX students. Data were collected through observation, questionnaires, and documentation, and were analyzed using descriptive statistics and paired t-tests. The findings revealed a significant improvement in students’ learning motivation after the implementation of interactive learning methods. The average motivation score increased from pre-action to post-action, accompanied by a decrease in the standard deviation, indicating greater uniformity in students’ motivation levels. Students became more active in discussions, more confident in expressing their opinions, and demonstrated higher enthusiasm during the learning process. Therefore, it can be concluded that interactive learning methods are proven effective in improving students’ learning motivation in ICT subjects.